Frozen (Burbank, CA Buena Vista Home Ent., 2014)
"Fearless optimist Anna sets off on an epic journey--teaming up with rugged mountain man Kristoff and his loyal reindeer Sven--to find her sister Elsa, whose icy powers have trapped the kingdom of Arendelle in eternal winter. Encountering Everest-like conditions, mystical trolls and a hilarious snowman named Olaf, Anna and Kristoff battle the elements in a race to save the kingdom."